Assessment of oxidative damage to proteins and DNA in urine of newborn infants by a validated UPLC-MS/MS approach. - Julia Kuligowski (Public Library of Science (PLoS), 2014)
The assessment of oxidative stress is highly relevant in clinical Perinatology as it is associated to adverse outcomes in newborn infants. This study summarizes results from the validation of an Ultra Performance Liquid Chromatography-tandem Mass Spectrometry (UPLC-MS/MS) method for the simultaneous quantification of the urinary concentrations of a set of endogenous biomarkers, capable to provide a valid snapshot of the oxidative stress status applicable in human clinical trials, especially in the field of Perinatology. The set of analytes included are phenylalanine (Phe), para-tyrosine (p-Tyr), ortho-tyrosine (o-Tyr), meta-tyrosine (m-Tyr), 3-NO2-tyrosine (3NO2-Tyr), 3-Cl-tyrosine (3Cl-Tyr), 2'-deoxyguanosine (2dG) and 8-hydroxy-2'-deoxyguanosine (8OHdG). Following the FDA-based guidelines, appropriate levels of accuracy and precision, as well as adequate levels of sensitivity with limits of detection (LODs) in the low nanomolar (nmol/L) range were confirmed after method validation. The validity of the proposed UPLC-MS/MS method was assessed by analysing urine samples from a clinical trial in extremely low birth weight (ELBW) infants randomized to be resuscitated with two different initial inspiratory fractions of oxygen.